Tunable Optical Metamaterial Enables Steganography, Rewriting, and Multilevel Information Storage - Zheng, Jianchen; Zhang, Yuzhao; Yu, Haibo; Wang, Jingang; Guo, Hongji; Qiu, Ye; Wang, Xiaoduo; Feng, Yu; Liu, Lianqing; Li, Wen Jung (Nano-Micro Letters, 2025)
In the realm of secure information storage, optical encryption has emerged as a vital technique, particularly with the miniaturization of encryption devices. However, many existing systems lack the necessary reconfigurability and dynamic functionality. This study presents a novel approach through the development of dynamic optical-to-chemical energy conversion metamaterials, which enable enhanced steganography and multilevel information storage. We introduce a micro-dynamic multiple encryption device that leverages programmable optical properties in coumarin-based metamaterials, achieved through a direct laser writing grayscale gradient strategy. This methodology allows for the dynamic regulation of photoluminescent characteristics and cross-linking networks, facilitating innovative steganographic techniques under varying light conditions. The integration of a multi-optical field control system enables real-time adjustments to the material’s properties, enhancing the device’s reconfigurability and storage capabilities. Our findings underscore the potential of these metamaterials in advancing the field of microscale optical encryption, paving the way for future applications in dynamic storage and information security. Highlights: 1 Proposed a dynamic grayscale gradient modulation system enabling multi-information analysis and encryption under multi-optical fields, establishing a new paradigm for multi-dimensional encryption of collaborative multispectral information. 2 Developed coumarin-based photo-responsive in situ reconstruction technology and constructed a multi-optical field coupled control system to achieve dynamic configuration of multi-information carriers. 3 Designed and fabricated a micro-dynamic multiple encryption device with integrated functions for information writing, erasing and rewriting, realizing stable information storage and dynamic destruction through micro/nano-optical keys.